2005
DOI: 10.1021/bp050048m
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Escherichiacoli Proteins under High Cell Density Fed‐Batch Cultivation with Overexpression of Phosphogluconolactonase

Abstract: In this study, we used proteomics to better understand the growth on glucose of Escherichia coli in high cell density, fed-batch cultures and the response to overexpression of plasmid-encoded 6-phosphogluconolactonase (PGL). Using liquid chromatography coupled to electrospray mass spectrometry, at least 300 proteins were identified in the cytosolic fraction of the six time points used to monitor the fermentation. The relative abundance changes of selected proteins were obtained by comparing the peak area of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 38 publications
(42 reference statements)
0
27
0
Order By: Relevance
“…coli was grown under fed-batch culture conditions as described by Wang et al (23), except that it was induced with IPTG for production of an 18-kDa protein. Also, the expression of either an LXR␣/RXR␣ heterodimer or elongin C was IPTG inducible, but E. coli was simply grown in batch cultures (see the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…coli was grown under fed-batch culture conditions as described by Wang et al (23), except that it was induced with IPTG for production of an 18-kDa protein. Also, the expression of either an LXR␣/RXR␣ heterodimer or elongin C was IPTG inducible, but E. coli was simply grown in batch cultures (see the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…In the light of our results, there is complete agreement with the idea that the role of the PGL enzyme is to facilitate the flow of metabolic intermediates through the PP shunt. The increases in the specific growth rate and biomass yield in the E. coli BL21(DE3) strain are associated with a faster and efficient supply by the PP pathway of aromatic amino acids and nucleic acids, as well as NADPH, for biomass synthesis (23). Our studies showed that when PGL is overexpressed, it increases the biomass yield, as well as the yield of a heterologous product (e.g., the 18-kDa protein), in high-cell-density cultures.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations